Formal and Informal Institutional Factors and Women Entrepreneurship in Egypt: A Qualitative Perspective - Rosfizah binti Md Taib (Tanjung Malim, 2024)
Formal and Informal Institutional Factors and Women Entrepreneurship in Egypt: A Qualitative Perspective by Rosfizah binti Md Taib